Komodifikasi Agama Dalam Iklan: Analisis Wacana Kritis Sara Mils Terhadap Iklan Biskuit Kokola Versi Mamah Dedeh - Sebastian, Andi (Universitas 17 Agustus 1945 Surabaya, 2022)
Commodification in religion raises many problems in religious traditions, debates arise in various circles. Some believe, the value of a religion should not involve money. Meanwhile, in the current era, it is difficult to stem the power and culture of the market. Religious leaders and missionaries now seem to be required to appear according to market needs. Mamah Dedeh is a preacher who has a religious appeal in advertisements. Setting the place and atmosphere with a religious theme also strengthens the attractiveness of the advertisement. By using symbols, as well as religious figures in advertisements, producers try to attract the majority of the Muslim population in Indonesia. The proliferation of forms of religiosity in the market creates a strong idea, that religion seems to be a commodity, and religion in the market becomes a general commodity. Aiming to describe and describe aspects of the commodification of religion, a case study method with a qualitative approach was chosen to examine advertising. The results show that there is a commodification of religion in advertising. Preachers or religious leaders are used to increase profits.